Inovasi Pengembangan Usaha Melalui Standardisasi Masa Simpan dan Pengawet Produk Gurita Olahan Masyarakat Pulo Aceh - Ramadhaniaty, Mutia; Octavina, Chitra; Suryani, Irma; Saputra, Ario; Sufie, Sultan (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Octopus is a biota with very high economic value, so it has become commercial and has high demand. Breuh Island is one of the suppliers of fresh octopus, both within and outside the Aceh region. One step to increase the selling price and long shelf life is to make the octopus into a pickled product. Kube Mangat is the fishery entrepreneur specializing in octopus processing in the Breuh Island area. Kube Mangat produces processed octopus in a very traditional way, both in terms of drying and storing the product. This service utilizes methods derived from research results, including proximate tests and microbiological tests. The results of this research explain that salted octopus products can last in excellent quality until the fourth month. The results of the research were disseminated to Kube Mangat partners and the Gampong Gugob community. This service has also successfully assisted Kube Mangat in obtaining a PIRT number, halal certificate, and trademark registration at the Ministry of Law and Human Rights. Because Kube Mangat has standardized its product packaging, it is currently suitable for entering the modern market.